Enhanced Transparency in Procurement through Voluntary Disclosure under the RTI Act 2005 - World Bank (Washington, DC, 2013)
Good practices reduce costs and produce timely results; poor practices lead to waste and delays and are often the cause for allegations of corruption and Government inefficiency. Enhanced transparency in procurement through voluntary disclosure under the Right to Information (RTI) Act (2005)' is one of the individual components of the larger initiative undertaken by Yashwantrao Academy of Development Administration (YASHADA) under the national resource centre for social accountability, and funded by the World Bank institute, New Delhi. Sound public procurement policies and practices are among the essential elements of good governance. The objective of the study is to: study the current procurement process; suggest measures to tackle the discrepancies by developing mechanisms; and enhance social accountability and transparency in the procurement process by focused implementation of right to information as a tool. The project takes into account the four pillar approach towards public procurement which believes that unless all the aspects of the function (i.e. efficiency, economy, fairness and transparency) are taken care of, the overall impact will not be evident. The focus of this project is mainly on social accountability. Obviously the focus of the study is on transparency and how by making the systems more transparent the other aspects of fairness, efficiency and economy can be pushed for reforming the procurement process.